Arkeologi Resort Hotel di Kawasan Wisata Candi Gedong Songo Bandungan - Kusuma, Arif jati; , Dr.Ir. Arya Ronald; , Ir. Nurhasan, MT (2016)
Archaeology Resort Hotel is a residential accommodation in which there are various facilities to support the activities of visitors. Of course, with the peculiarities owned Archaeology Resort Hotel will make its own character ranging from the look of the exterior and interior. Archaeology Resort Hotel itself will have a very private residential housing for the residents. With a view and a distinctive atmosphere it is expected will make visitors feel at home stay and will eventually and want to come back again. Due to experience what visitors get in Archaeology Resort Hotel, not found in other hotel resort. Bandungan is one that is in the District of Semarang district under the rule of the city of Semarang. Bandungan is an area that is located on a plateau that has a lot of potential. One of these tourism potentials, ranging from nature, culture, education and artificial. This is supported by wonderful natural conditions and cool air. the existence of Archaeology Resort Hotel is expected to be a positive value for tourism activities in the district Bandungan. Later the design concept of the physical appearance of the building both exterior and interior indirectly reflects the inability of the visualization of Candi Gedong Songo as its object.